Embriotoxicidad del bromato de potasio en raton (Mus musculus ) - Landeo, Grecia (2007)
The effect of potassium bromate (KBr0 3 )on preimplantation mouse embryo development was evaluated in vivo . Pregnant mice were treated with unique dose of KBr0 3 (68,5 mg/kg of corporal weight; n= 8) and a control (C) provided with distilled water (n= 7) on day 1; at the fourth day of pregnancy, females were sacrifi ced, embryos were fl ushed from oviducts and uterine horns for evaluation. KBr0 3 causes a delay in the embryonic development, 76,9±7,8 y 11,2±5,5 percent of blastocyst and morulaes respectively in the control group comparing with 34,8±11,2 y 49,3±11,9 percent of the same relation in the treated group, showing signifi cative difference (p<0,05). Concerning to the embryonic quality, an increase in the percentage of low quality embryos (degree III and degenerated) in the treated group is observed, but this difference is not statistically signifi cant (p>0,05). In conclusion we can say that KBr0 3 produces a harmful effect on the embryo causing a delay on its development.